Assessing beginner arabic proficiency in saudi foundation programs: Aligning Arabic-as-a-foreign-language learning outcomes with the Imtāʿ reference framework at the preparatory level - Elhudaybi, Ali Abdulmohsen; Alharbi, Wael Matar Hasan (Research Journal in Advanced Humanities, 2026)
Saudi foundation (preparatory-year) programs increasingly host Arabic-as-a-foreign-language (AFL) learners whose progression must be reported in ways that are interpretable across institutions. Yet beginner assessment practices often remain local, outcome statements are under-specified, and score reports are weakly linked to externally described proficiency levels. This study advances a replicable alignment-and-linking approach that connects (i) course learning outcomes, (ii) assessment blueprints and rating scales, and (iii) score interpretations to the Imtāʿ Reference Framework at the preparatory level. We argue that such alignment strengthens validity arguments, improves fairness, and enables mobility by making beginner proficiency claims auditable and comparable. Methodologically, the paper combines (a) outcomes-to-descriptor mapping by an expert panel, (b) development of an Imtāʿ-aligned beginner proficiency assessment covering listening, reading, interaction, and guided writing, (c) rater training and many-facet Rasch measurement for productive tasks, and (d) standard-setting (bookmark) to locate cut scores for preparatory sublevels. Results from a synthetic cohort dataset (N = 360) illustrate how the workflow yields high content relevance indices for mapped outcomes (median Aiken’s V = .86), stable measurement for the receptive test (Rasch person reliability = .82), manageable rater severity after calibration (MFRM severity range < 0.8 logits), and interpretable distributions of learners across Imtāʿ preparatory sublevels. The study contributes a practical blueprint for institutions seeking to operationalize Imtāʿ at entry and early-exit points, with recommendations for outcome rewriting, item banking, rater certification, and reporting formats that communicate what learners can do with Arabic at the preparatory stage.